THE MODERATING ROLE OF LEVERAGE ON CORPORATE BONDS YIELD - Pardomuan Sihombing; Amanda Yosephine Bonowati; Elia Zakchona (Universitas Udayana, 2024)
This study aims to identify the effect of bond credit rating, firm size, profitability, andliquidity on the yield to maturity (YTM) of listed Indonesian corporate bonds, withleverage ratio as a moderating variable. A panel data multi-linear regression with the fixedeffect estimator was used to investigate the YTM of 25 listed corporate bonds from 2019 to2021. The sample data comprise complete financial reports published in the Indonesia StockExchange (IDX) market and operations in the non-financial sector to increase the accuracyof information obtained. The results show that profitability proxied to return-on-asset(ROA) and firm size positively affect the YTM, while the liquidity ratio proxied to thecurrent ratio (CR) had a negative influence. As a moderating variable, leverage proxied tothe debt-to-equity ratio (DER) positively moderates the effect of CR, DER negativelymoderates the effect of ROA and DER cannot moderate the bond’s credit rating to influencethe YTM. However, the bond’s credit rating does not affect the YTM. The analysis ofcorporate bonds is a relatively uncommon study in Indonesia, and significant implicatingfor policymakers, underscoring the importance of meticulous management of CR and DER,which can decrease the YTM.